2015
DOI: 10.1523/jneurosci.4775-14.2015
|View full text |Cite
|
Sign up to set email alerts
|

Computational Substrates of Social Value in Interpersonal Collaboration

Abstract: Decisions to engage in collaborative interactions require enduring considerable risk, yet provide the foundation for building and maintaining relationships. Here, we investigate the mechanisms underlying this process and test a computational model of social value to predict collaborative decision making. Twenty-six participants played an iterated trust game and chose to invest more frequently with their friends compared with a confederate or computer despite equal reinforcement rates. This behavior was predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
159
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(195 citation statements)
references
References 49 publications
21
159
2
Order By: Relevance
“…Unexpected positive outcomes resulting from help of another person elicit prediction error signals, that is, signals that resemble the ones known to drive reinforcement learning in the monkey brain (17,18). Our results indicate that basic learning mechanisms are also used during complex social learning, which is in line with previous studies (13,(35)(36)(37)(38). Going further, our findings show how classical learning mechanisms shape otherregarding motivational states such as empathy.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Unexpected positive outcomes resulting from help of another person elicit prediction error signals, that is, signals that resemble the ones known to drive reinforcement learning in the monkey brain (17,18). Our results indicate that basic learning mechanisms are also used during complex social learning, which is in line with previous studies (13,(35)(36)(37)(38). Going further, our findings show how classical learning mechanisms shape otherregarding motivational states such as empathy.…”
Section: Discussionsupporting
confidence: 90%
“…Forty healthy men (mean age, 22.7; SE, 0.41) participated in the study. They were randomly assigned to the experimental and the control group with no age difference between the groups [t (38) …”
Section: Methodsmentioning
confidence: 99%
“…Moreover, it has been demonstrated that social context can modulate neural reward signals (i.e., Bault, Pelloux, Fahrenfourt, Ridderinckhof, & van Winden, 2015;Fareri, Chang, & Delgado, 2015;Fareri & Delgado, 2014;Fareri, Niznikiewicz et al, 2012;Inagaki et al, 2015) and neural representations of decision value (Strombach et al, 2015). Interpretations of these findings rely thus far on a theorized psychological preference for social connection (e.g., need to belong; Baumeister & Leary, 1995;Bowlby, 1969).…”
Section: Discussionmentioning
confidence: 99%
“…Dissimilarity between individuals negatively influences assessments of entitativity, the extent to which the parties perceive that they are part of a single group [8], and is associated with lower levels of trust [53]. Research suggests the relationship between collaboration as a member of a perceived group and increased levels of trust is deeply rooted in our neurobiology [14], and this relationship is well-supported in the extant literature from a wide variety of academic disciplines [33]. Thus, we posit:…”
Section: Perceptions Of News Sharersmentioning
confidence: 91%
“…This is because unlike the more superficial approaches to discerning similarity, the identification of common belief structures requires knowledgebased familiarity, a particularly strong antecedent of trust [19]. Because SNSs are used to project a desired social identity that exemplifies the beliefs of the individual [14], posts serve as cues which allow network members to evaluate the degree of cognitive homogeneity that exists between themselves and other network members [20]. Individuals that perceive themselves as having similar opinions and thoughts as other network members are likely to connect more deeply than individuals that perceive themselves as different [48].…”
Section: H1b: Social Tie Variety Is Negatively Related To Trust In Nementioning
confidence: 99%